Nonoperative Management of Gunshot Injury of Abdomen in A 10-Year-Old Boy - Karabulut, Ramazan (Springer India, 2012)
Selective conservative therapy has not gained popularity in the management of abdominal gunshot wounds, and standard practice is mandatory exploration irrespective of clinical signs and symptoms. In this report, we describe a 10-year-old boy with an abdominal gunshot wound with stable vital signs who was managed conservatively.